2009
DOI: 10.1080/07420520903044315
|View full text |Cite
|
Sign up to set email alerts
|

Daily and Seasonal Variation in the Spectral Composition of Light Exposure in Humans

Abstract: Light is considered the most potent synchronizer of the human circadian system and exerts many other non-image forming effects, including those that affect brain function. These effects are mediated in part by intrinsically photosensitive retinal ganglion cells that express the photopigment melanopsin. The spectral sensitivity of melanopsin is greatest for blue light at approximately 480 nm. At present, there is little information on how the spectral composition of light to which people are exposed varies over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
90
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 40 publications
17
90
1
1
Order By: Relevance
“…Photoperiod is the most obvious factor associated with season and both the intensity and spectral composition of light to which people are exposed vary with season (36). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photoperiod is the most obvious factor associated with season and both the intensity and spectral composition of light to which people are exposed vary with season (36). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, recent reports showed that prolonged darkness or lack of light in rodents induces a depression-like state associated with structural brain changes (46), whereas complete blindness increases depression risk (47). Likewise, long-term changes in ambient light daily profile, such as light therapy, seem to restore normal mood regulation (1,2), and the spectral composition of light changes across the seasons (48). Interestingly, blue-enriched light seems to be equally effective as (visually) brighter white light in the treatment of SAD (49), and a polymorphism in the melanopsin gene has recently been associated with SAD (50).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the light-induced modulation of amygdala activity may correspond to one of the underlying reasons for the therapeutical property of light in mood disorders. Light therapy is the treatment of choice of seasonal affective disorder (SAD), and the relative contribution of blue light to overall natural light exposure is smaller during the winter than during the summer (Thorne et al, 2009). However, it is still uncertain as to whether the longterm effects of repeated exposures on mood as used in light therapy are related to the acute modulation of brain activity to tasks that do not involve emotion.…”
Section: Cerebral Correlates Of Light Impacts' On Cognitive Performancementioning
confidence: 99%